Implementasi Sistem Pengendalian Manajemen Berbasis Prinsip Good Corporate Governance untuk Meningkatkan Kinerja Pelayanan Publik pada Kantor Dispendukcapil Kota Surabaya - Utami, Yekti; Soeherman, Bonnie (Jurnal EMT KITA, 2025)
The purpose of this study is to analyze the implementation of management control systems based on the principles of good corporate governance to improve public service performance at the Civil Registry and Civil Registration Office of Surabaya City. This research was conducted at the Civil Registry and Civil Registration Office located at Jl. Tunjungan No.1-3, Genteng, Kec. Genteng, Surabaya, East Java. The research is planned for 3 (three) months starting from May to July 2024. The type of approach in this research is descriptive qualitative. Data collection technique is through interviews. After collecting data in the above stages, the stages in the qualitative data processing technique according to Miles and Huberman. The conclusion of this study is that in implementing the Principles of Good Corporate Governance consisting of the values of transparency, accountability, responsibility, independence, fairness, and equality, the Civil Registry and Civil Registration Office in Surabaya City can improve its service performance by providing more responsive, efficient, fair, and equal services to all citizens. Transparency in procedures and policies provides easy access for the public, while accountability ensures that every action or decision can be accounted for. Employee responsibility and the independence of the Civil Registry and Civil Registration Office in Surabaya City ensure integrity and efficiency in service, while fairness and equality ensure that every individual is treated fairly without discrimination. By consistently applying these values, the Civil Registry and Civil Registration Office in Surabaya City can enhance public trust and provide more responsive, efficient, and quality services.